Cross-resistance to cytosine arabinoside in human acute myeloid leukemia cells selected for resistance to vincristine - Gunduz, U.; Baran, Y.; Uralsup, A.U. (Experimental Oncology, 2006)
Aim: The goals of the study were to reveal the involvement of P-glycoprotein (P-gp), the product of multidrug resistance 1 gene (MDR1) in cellular resistance to vincristine (VCR) and investigate cross-resistance against cytosine arabinoside (Ara-C) in HL60 and HL60/VCR cell lines. Methods: HL60 cells (human acute myeloid leukemia cell line) were cultured on medium with 1–50 nM of VCR for 4–6 weeks, and VCR resistant cells (HL60/VCR) were selected. The viability of cells was assessed by MTT assay and the expression of MDR1 gene was detected by RT-PCR. Results: No expression of MDR1 gene was revealed in HL60 cells, but MDR1 started to be expressed after incubation of cells with 2 nM of VCR and its expression level elevates with increase of agent concentration. MTT test has shown that HL-60/VCR cells were 75-fold more resistant to VCR and 42-fold higher resistant to cytosine arabinoside (Ara-C) compared to sensitive HL60 cells. Conclusion: Aquired resistance to VCR and cross-resistance to Ara-C correlates with MDR1 gene expression in vitro.